TEACHING AND LEARNING PRACTICES IN CHEMISTRY PRACTICAL WORK OF MALAYSIAN MATRICULATION PROGRAMME: A NEEDS ANALYSIS - Nurul Fatni Abdussyukur; Rohaida Mohd Saat; Norlidah Alias (MOJES: Malaysian Online Journal of Educational Sciences, 2021)
The importance of chemistry practical work in enhancing students' performance and 21st-century skills has been highlighted in the literature. However, Malaysian Matriculation chemistry lecturers were lack of knowledge in the 21st-century pedagogies and practiced the cook-book recipe teaching style which proved ineffective in enhancing students’ 21st-century skills. Therefore, there was a need to develop a pedagogical module of chemistry practical work for the Malaysian Matriculation Programme based on 21st- century skills. To develop a comprehensive pedagogical module, it was aimed to identify the needs of the development of the module based on lecturers’ views from the Matriculation Programme. Hence, this article focuses on the needs analysis phase attempted to identify lecturers’ current teaching and learning practices in chemistry practical lessons. Therefore, there were five chemistry matriculation lecturers have been interviewed and data were analyzed using thematic content analysis. The emergent themes revealed that the current teaching and learning of chemistry curriculum in the Matriculation Programme is exam-oriented. The impacts of the exam-oriented curriculum are pronounced on the learning objectives, teaching and learning activities, assessment, learning hours were towards examination compared to the importance of practical work itself. Then, the issues on limited instructional media and teaching resources also emerged. Hence, it is proven that the 21st-century pedagogies were less been emphasized in the Matriculation Programme practical work lessons. As a result, the development of the pedagogical module of chemistry practical work in the next stage of